On the Solution of Reduced Wave Equation with Damping - Misir, Adil (Communications in Mathematics and Applications, 2010)
In this paper we find particular solutions of Reduced wave equation with damping in the form Δ u+k^2n( x) u+μ abla u=0, R^n, μR and n(x) is a continuous function on Ω, by making use of Fundamental solution u=(ikR)R of the scalar Helmholtz equation and employing a variation of constant technique. Moreover, some examples are given to illustrate the importance of our results.